The war for the public mind : political censorship in nineteenth-century Europe - Goldstein, Robert Justin (Praeger, 2000)
Presenting a comprehensive discussion of the censorship of books, newspapers, carricutures, theatre and film, this volume provides an analytical introductory survey and six chapters that summarize the 19th-century censorship practices in the six major countries of continental Europe.